Cross-cultural analysis of gen Z customer behavior on fads : a comprative study of Korean and Czech youth - Ahn, Jungmin (2025)
The purpose of the thesis is to conduct a cultural analysis of Gen Z consumer behavior on fads in South Korea and the Czech Republic, two countries with different cultural backgrounds. The study applied a qualitative research technique, conducting 17 in-depth interviews (9 Korean respondents and 8 Czech respondents) with thematic analysis for data processing. From the results, some main findings (differences and similarities) were revealed. It was clearly shown that fads are significantly influencing Generation Z across cultures, but Koreans are more attached to them, often viewing trends as a form of social connection and validation, while Czechs view them as a fleeting phenomenon, prioritizing practicality and personal values. Their motivation and attitude towards fads were different from each other. Additionally, social media has a crucial impact on Generation Z, especially in terms of trend diffusion. Regarding decision drivers, price, quality, and practicality were the most important considerations for them to adopt trends; however, Koreans were more willing to follow due to social cues. Overall, all these findings demonstrate that Gen Z is highly associated with fads, yet has different perceptions, attitudes, and responses towards them depending on their social norms, which indicates that cultural backgrounds significantly shape consumer behavior within fad adoption. Based on the findings, the paper suggests that marketers should take different approaches, aligning with local cultures and utilizing social media to engage Gen Z consumers with fad-based products.